2016
DOI: 10.1371/journal.pone.0166606
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Gemcitabine Chemotherapy followed by Concurrent IMRT Simultaneous Boost Achieves High R0 Resection in Borderline Resectable Pancreatic Cancer Patients

Abstract: BackgroundTo study the feasibility of down stage the borderline resectable pancreatic cancer (BRPC) to resectable disease, we reported our institutional results using an intensity-modulated radiation therapy (IMRT) simultaneous integrated boost (SIB) dose escalation approach to improve R0 resectability.MethodsWe reviewed our past 7 years of experience of using neoadjuvant induction chemotherapy with Gemcitabine followed by concurrent chemoradiaiton for BRPC. During the concurrent, chemo was 5-FU and radiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…NT in pancreatic cancer continues to be controversial. Its use in pancreatic cancer has previously demonstrated higher likelihood of achieving R0 margins in borderline resectable disease (18,(21)(22)(23)(24)(25). Achieving an R0 resection over R1 has demonstrated a significant improvement in median survival by 6 months (26).…”
Section: Discussionmentioning
confidence: 99%
“…NT in pancreatic cancer continues to be controversial. Its use in pancreatic cancer has previously demonstrated higher likelihood of achieving R0 margins in borderline resectable disease (18,(21)(22)(23)(24)(25). Achieving an R0 resection over R1 has demonstrated a significant improvement in median survival by 6 months (26).…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14] Several studies have compared postoperative complication rates for patients undergoing pancreaticoduodenectomy after neoadjuvant therapy and those undergoing primary pancreatic resection. 15,16 Teng et al 9 found that neoadjuvant chemoradiation therapy was associated with an increase in transfusion requirement and superficial SSI. However, the study did not find any associated 30-day mortality with the use of neoadjuvant chemoradiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike CT and MRI, to date, the use of PET to adapt the radiotherapy plan on a daily basis has not been investigated. On the other hand, there are several papers reporting on the usefulness of PET imaging for the optimisation of target volume delineation [45][46][47][48][49][50][51] and the delivery of a radiotherapy boost 52,53 to improve the response outcome for patients with pancreatic cancer treated with radiotherapy (table 2).…”
Section: Pancreatic Cancermentioning
confidence: 99%